2004
DOI: 10.1016/j.ejcts.2004.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting patency of internal thoracic artery graft: clinical and angiographic study in 1434 symptomatic patients operated between 1982 and 20021

Abstract: Even in a patient cohort that had adverse symptoms, excellent LITA and RITA patency was achieved which almost remained constant through all time intervals studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 22 publications
(11 reference statements)
3
45
1
6
Order By: Relevance
“…Risk difference analyzes showed 40 SSI prevented per 1000 coronary bypass surgeries with an off-pump approach. Other studies showed the used mammary artery during coronary bypass surgery have superior patency rates of >90% up to 15 years of follow-up [23]. Therefore it is preferred to use the mammary artery if needed both; however, the disadvantage is the reduction of blood supply of the sternum.…”
Section: Incidence Of Ssi Discussionmentioning
confidence: 99%
“…Risk difference analyzes showed 40 SSI prevented per 1000 coronary bypass surgeries with an off-pump approach. Other studies showed the used mammary artery during coronary bypass surgery have superior patency rates of >90% up to 15 years of follow-up [23]. Therefore it is preferred to use the mammary artery if needed both; however, the disadvantage is the reduction of blood supply of the sternum.…”
Section: Incidence Of Ssi Discussionmentioning
confidence: 99%
“…In our unselected patients, the TF-1 rate was 13.2% and freedom from TF-1 is correspondingly 86.8%. Interestingly, the five years patency rate have been reported to be 72% of Saphenous vein grafts and 88% -92% for internal mammary artery grafts [14] [15]. In plain words, PCI with a drug eluting stent appears to have almost the same durability as mammary grafts after five years observation.…”
Section: The Durability Of Pci With Drug Eluting Stentsmentioning
confidence: 94%
“…Graft failure is therefore an expected finding in this population, and the overall patency rate will be correspondingly lower in this selected population. 5 In response to Drs Shah, Baker, and Knight, the lower patency rates compared with the studies by Shah et al 6,7 may reflect differences in definitions, because we defined a severe stenosis as being Ն70% (versus Ն80% in their studies), and may reflect differences in patient populations. We did not provide patency information of Y versus sequential grafts versus free grafts because the number of grafts in some of the subgroups was rather small.…”
Section: Responsementioning
confidence: 95%